The Challenge by Multiple Environmental and Biological Factors Induce Inflammation in Aging: Their Role in the Promotion of Chronic Disease - Bachmann, María Consuelo; Bellalta, Sofía; Basoalto, Roque; Gómez-Valenzuela, Fernán; Jalil, Yorschua; Lépez, Macarena; Matamoros, Anibal; von Bernhardi, Rommy (Frontiers in Immunology, 2020)
The aging process is driven by multiple mechanisms that lead to changes in energy production, oxidative stress, homeostatic dysregulation and eventually to loss of functionality and increased disease susceptibility. Most aged individuals develop a chronic low-grade inflammatory state, which is an important risk factor for morbidity, physical and cognitive impairment, frailty and death. Several environmental factors may play an important role for modifying the inflammatory state. On the other hand, at any age, chronic inflammatory diseases are major causes of morbimortality, affecting up to 5–8% of the population of industrialized countries. Genetics accounts for only a small fraction of chronic-inflammatory diseases, whereas environmental factors appear to participate, either with a causative or a promotional role in 50-75% of patients. Several of those changes depend on epigenetic changes that will further modify the individual response to stimuli. Furthermore, the interaction between inflammation and the environment offers important insights on aging and health. These conditions, often depending on the individual’s sex, appear to lead to decreased longevity and physical and cognitive decline. In addition to biological factors, the environment is also involved in the generation of psychological and social context that could result in stress. Poor psychological environments and other sources of stress also result in increased inflammation. However, the mechanisms underlying the role of environmental factors and nutrition on the regulation of inflammation are poorly understood. Furthermore, whereas nutrients and certain deleterious environmental factors can result in the generation of oxidative stress-mediated by the increased production of reactive oxygen and nitrogen species, endoplasmic reticulum stress, and inflammation, nutrition (polyunsaturated fatty acids) and behavioral factors (exercise) confer protection against inflammation, oxidative and endoplasmic reticulum stress, and thus ameliorate their deleterious effect. Here, we discuss processes and mechanisms of inflammation associated with environmental factors and behavior, their links to sex and gender, and the impact on aging.